Žáci, učitelé a Cvrček: „dělali jsme Cvrčka“ – a co dál? - Nováková, Eva (Učitel matematiky, 2021)
Several examples are given of creative application of tasks from the Cricket category (Pre-ѐcolier) of Mathematical Kangaroo competition for the education on the primary school. Such tasks may serve as inspiration for the development of professional competence of teachers in the context of constructivistic culture of education and learning.